2019
DOI: 10.1108/ijchm-01-2019-0091
|View full text |Cite
|
Sign up to set email alerts
|

Prices of short-stay accommodation: time series of a eurozone country

Abstract: Purpose This paper aims to provide a reliable statistical model for time-series prices of short-stay accommodation and overnight stays in a eurozone country. Design/methodology/approach Exploiting the unit root feature, the cointegrated vector autoregressive model solves the problem of misspecification. Subsequently, variables are modelled for a long-run equilibrium with included deterministic variables. Findings The empirical results confirmed that overnight stays for foreign tourists were positively asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…As one exception, Herrmann and Herrman studied the effects of large-scale events on hotel prices and showed that average rates fluctuated greatly over time during Germany's Oktoberfest [20]. Gricar and Bojnec studied seasonal fluctuations in hotel pricing from a longitudinal standpoint, and their findings proved the rationale for seasonal pricing [21]. Law and colleagues have examined room rate fluctuations in various settings.…”
Section: Research On Hotel Room Ratesmentioning
confidence: 99%
“…As one exception, Herrmann and Herrman studied the effects of large-scale events on hotel prices and showed that average rates fluctuated greatly over time during Germany's Oktoberfest [20]. Gricar and Bojnec studied seasonal fluctuations in hotel pricing from a longitudinal standpoint, and their findings proved the rationale for seasonal pricing [21]. Law and colleagues have examined room rate fluctuations in various settings.…”
Section: Research On Hotel Room Ratesmentioning
confidence: 99%
“…The P2P accommodation phenomenon has been studied in the literature from different points of view: regulations (Williams and Horodnic, 2017), price and revenues (Gri car and Bojnec, 2019;Guttentag and Smith, 2017;Zervas et al, 2017), economic impact on the traditional offer (Heo, 2016;Möhlmann, 2015) and consumer choice motives (Botsman and Rogers, 2010;Guttentag, 2015;Guttentag et al, 2018;Pappas, 2017;Piscicelli et al, 2015). Although explored from different perspectives, the P2P accommodation phenomenon requires further investigation, as the literature is still fragmented (Dolnicar, 2019;Sainaghi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The empirical results confirmed that overnight stays for foreign tourists were positively associated with the prices of short-stay accommodation. Tourists could benefit either from greater price stability or from differentiated seasonal prices, which are important in the promotion of the price attractiveness of the tourist destination [9]. The findings also reveal that the local tourist accommodation supply has experienced an especially dynamic, sustained growth over the past decade.…”
Section: Literature Reviewmentioning
confidence: 87%